RFT1 Protein Affects Glycosylphosphatidylinositol (GPI) Anchor Glycosylation - Gottier, Petra (J Biol Chem, 2017)
The membrane protein RFT1 is essential for normal protein N-glycosylation, but its precise function is not known. RFT1 was originally proposed to translocate the glycolipid Man(5)GlcNAc(2)-PP-dolichol (needed to synthesize N-glycan precursors) across the endoplasmic reticulum membrane, but subsequent studies showed that it does not play a direct role in transport. In contrast to the situation in yeast, RFT1 is not essential for growth of the parasitic protozoan Trypanosoma brucei, enabling the study of its function in a null background. We now report that lack of T. brucei RFT1 (TbRFT1) not only affects protein N-glycosylation but also glycosylphosphatidylinositol (GPI) anchor side-chain modification. Analysis by immunoblotting, metabolic labeling, and mass spectrometry demonstrated that the major GPI-anchored proteins of T. brucei procyclic forms have truncated GPI anchor side chains in TbRFT1 null parasites when compared with wild-type cells, a defect that is corrected by expressing a tagged copy of TbRFT1 in the null background. In vivo and in vitro labeling experiments using radiolabeled GPI precursors showed that GPI underglycosylation was not the result of decreased formation of the GPI precursor lipid or defective galactosylation of GPI intermediates in the endoplasmic reticulum, but rather due to modifications that are expected to occur in the Golgi apparatus. Unexpectedly, immunofluorescence microscopy localized TbRFT1 to both the endoplasmic reticulum and the Golgi, consistent with the proposal that TbRFT1 plays a direct or indirect role in GPI anchor glycosylation in the Golgi apparatus. Our results implicate RFT1 in a wider range of glycosylation processes than previously appreciated.